PENGARUH TAX AVOIDANCE TERHADAP COST OF DEBT DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI PEMODERASI PADA PERUSAHAAN MENURUT RATING SCORE HUTANG PADA PEFINDO - Husein, Hartina; Usmany, Alfrin; Kriswantini, Dwi; Tjio, Sari T (Jurnal Daya Saing, 2024)
The inconsistency of previous research results regarding the relationship between tax avoidance and the cost of debt is the background for this research. The complexity of determining a company's capital structure in theory, preferability trade off of debt and equity, consideration of benefits and costs are the reasons for tax savings as overvalued deductible expense explain the reasons for the choice of debt financing which is given more priority compared to financing from the capital side. On the other hand, choosing a debt over equity source creates a risk of expropriation between investors and creditors, therefore this research uses institutional ownership variables to answer the question of whether this variable can associate the relationship between tax avoidance and the cost of debt. By using a sample of companies on PEFINDO in Indonesia this research questions are still unanswered. Overvaluing assets, selecting accounting method or principle of accounting standards that have the potential to increase deductible costs through increasing depreciation, amortization and pension fund expenses are some of the activities that increase corporate tax avoidance Key Words: Cost of debt, Tax avoidance, Institutional Ownership